Pyrenean oak forests under global change - integrating projected suitable areas in management plan - Passos, Isabel (2023)
Forests provide broad ecosystem services (ES), and their contribution to regulation and maintenance services (e.g. carbon sequestration, soil formation, habitat protection, erosion control) explains why forest recovery/expansion is an effective nature-based solution for climate change mitigation. Thus, forest restoration measures must integrate results about expected changes in species distribution, as future climate change may promote range shifts and suitable habitat loss, followed by species turnover. Expected changes in forest species’ potential distribution should be considered in forest ecosystem restoration planning actions, to increase long-term success, and enhance ES at long term. Pyrenean oak (Quercus pyrenaica) is a native species to the western Mediterranean Basin, and a structural tree in central and northern inland Portugal forests, together with pedunculate oak (Q. robur subsp. broteroana). Despite the extensive potential growing area, it has a fragmented distribution due to fast-growing forest species reforestation, agriculture, and other land-use impacts. In this work, we used species distribution models (SDMs) to assess changes in suitable areas for the Pyrenean oak under two climate change scenarios (SSP370 and SSP585), aiming to guide forest recovery measures dedicated to ES enhancement at long term. The Pyrenean oak's entire native range was considered in the models’ calibration, and different algorithms were used. The results suggest that the species' total suitable area will be negatively affected by climate change in the future, with a clear suitability turnover with other oak species, namely more dryness-adapted ones. Overall, Quercus pyrenaica suitable area will decline, and management actions should consider this aspect in future restoration plans, especially at the edges of its current distribution area